Management of acute paracetamol poisoning in a tertiary care hospital - Senarathna, S.M.D.K.G.; Ranganathan, Shilani Sri; Dawson, A.H.; Buckley, N.; Fernandopulle, B.M.R. (Sri Lanka Medical Association, 2008)
Objectives To compare the management of acute paracetamol poisoning with the best evidence available, and to determine the effect of plasma paracetamol level estimation on the management. Design Descriptive study with an intervention. Setting Medical wards of the National Hospital of Sri Lanka, Colombo. Patients Patients admitted with a history of acute paracetamol poisoning. Intervention Measurement of plasma paracetamol. Methods Data were obtained from the patients, medical staff and medical records. Plasma paracetamol was estimated between 4-24 hours of paracetamol ingestion. The current management practices were compared with the best evidence on acute paracetamol poisoning management. Results 157 patients were included. The mean ingested dose of paracetamol was 333 mg/kg body weight. Majority of the patients (84%) were transfers. Induced emesis and activated charcoal were given to 91% of patients. Nacetylcysteine was given to 66, methionine to 55, and both to 2. A clinically important delay in the administration of antidotes was noted; 68% of patients received antidotes after 8 hours of the acute ingestion. Only 31 (26%) had paracetamol levels above the Rumack- Matthew normogram. 74 patients received an antidote despite having a plasma paracetamol level below the toxic level according to the normogram. Interpretation Management of acute paracetamol poisoning could be improved by following best available evidence and adapting cheaper methods for plasma paracetamol estimation.
Keywords: acute paracetamol poisoning; N-acetylcysteine; methionine